The effects cross-fostering and melatonin supplementation on the oxidant/antioxidant status and development of hypertensioni In spontaneously hypertensive rats - -, Sirajudeen (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
This study examined the effects of either cross-fostering or melatonin supplementation alone or in combination on the development of hypertension and renal antioxidanVoxidant system in SHR and WKY rats. One-day-old offspring of SHR and WKY dams received melatonin ( 1 Omg/kg body weight) from gestation day-1 cross-fostered to opposite strain of dam and these male offspring continued to receive melatonin (10mg/kg body weight) up to 16 weeks of age. Systolic blood pressure (SSP) of male offspring was recorded at the age of 4, 6, 8, 12 and 16 weeks, and the kidneys were collected for the estimation of antioxidanVoxidant status at the end of each age category. In cross-fostered SHR, SSP was significantly lower than that in SHR controls till the age of 12 weeks and TSARS was lower at 4 weeks. SSP in melatonin treated SHR offspring remained significantly lower till the age of 16 weeks when compared to untreated SHR GPx and GST activities were significantly higher at the age of 16 weeks, and total glutathione level was significantly higher at 4, 12 and 16 weeks in melatonin treated SHR when compared to untreated SHR In melatonin supplemented crossfostered SHR, SSP was significantly lower at the age of 12 and 16 weeks when compared to untreated cross-fostered SHR, but was significantly lower throughout the experimental period when compared to untreated in-fostered SHR Activities of GPx and GST were higher in melatonin-treated cross-fostered SHR aged 16 weeks, when compared to age-matched SHR and non-melatonin supplemented crossfostered SHR This study suggests that both melatonin supplementation and cross-fostering reduce the rate of rise in SBP. A combination of melatonin supplementation and cross-fostering however did not confer any additional impact on the blood pressure lowering effect of either melatonin or cross-fostering alone.